1988
DOI: 10.2134/agronj1988.00021962008000020022x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation in a White Clover‐Fescue Pasture Using Three Methods of Nitrogen‐15 Application and Residual Nitrogen‐15 Uptake

Abstract: It is essential that the 15 N source and method of labeling should not introduce significant errors into the estimation of N2 fixed in plants. This study, which was conducted in 1984 and continued in 198S, compares N 2 fixation measurements based on the repeated or rotated application of 15 N-Iabeled (NH 4 ) 2 S0 4 on plots of white clover (Trifolium repens cv. Zapican)-fescue (Festuca arundinacea cv. Tacuabe) sward with values obtained from plants that relied solely on residual ' 5 N uptake. The soil used was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…These comparisons would however have been valid and more meaningful if they had simply been restricted to an examination of the relative 15N enrichments or % Ndff within only the legumes harvested at 90 DAP (even though they had no reference crop). Furthermore, Hardarson et al (1984b) and Labandera et al (1988), indicated that direct 15N isotopic parameters, such as % ~SN a.e. or % Ndff in fixing crops are more sensitive and perhaps result in more accurate relative comparisons than other isotope-derived estimates (e.g., those involving reference crops).…”
Section: Non-obligatory Requirement For Reference Cropsmentioning
confidence: 99%
See 2 more Smart Citations
“…These comparisons would however have been valid and more meaningful if they had simply been restricted to an examination of the relative 15N enrichments or % Ndff within only the legumes harvested at 90 DAP (even though they had no reference crop). Furthermore, Hardarson et al (1984b) and Labandera et al (1988), indicated that direct 15N isotopic parameters, such as % ~SN a.e. or % Ndff in fixing crops are more sensitive and perhaps result in more accurate relative comparisons than other isotope-derived estimates (e.g., those involving reference crops).…”
Section: Non-obligatory Requirement For Reference Cropsmentioning
confidence: 99%
“…These results indicate that the effect of frequent, small 15N fertilizer additions on estimates of N 2 fixed, if any, were rather small, and may be of little consequence especially at high levels of fixation. and Labandera et al (1988) suggested that ~5N uptake from residual N in soil is often insignificant compared to the substantial N uptake from recent applications, for which reason they obtained satisfactory estimates from such sequential ~SN additions. Based on field studies, Steele and Littler (1987) have similarly suggested that estimates of N 2 fixed, following multiple application of 15N on plots appear to be mostly influenced by the most recent addition of 15N.…”
Section: Frequency Of 15n Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In isotope dilution the mineral N in soil is enriched or depleted with 15N by adding fertilizer N. Because the nitrogen fixed by the legume is close to natural abundance values of 15N, transfer of this N to a companion grass makes the 15N content of the grass closer to the natural abundance value. Isotope dilution is more sensitive for detecting N transfer than total N difference because it is yield independent (Labandera et al, 1988). Also, N transfer can be measured in the presence of fertilizer N applications (Boiler and Nosberger, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Some methodoligical problems have recently been reported by Broadbent et al (1982) and Chalk (1985), most common of which is the selection of a satisfactory reference crop. Some attempts have been made to determine experimental errors resulting from adopting various approaches of the N-15 methodology, and possible solutions Labandera et al, 1988;Witty and Ritz, 1984). These however represent only a small proportion of the 15N based measurements of N 2 fixation, and several aspects of the methodology have frequently been adopted without adequate verification.…”
Section: Introductionmentioning
confidence: 99%